Federalism and the courts in Africa design and impact in comparative perspective - Kössler, Karl 1979- (Routledge, 2020)
"This volume examines the design and impact of courts in African federal systems from a comparative perspective. Recent developments indicate that the previously stymied idea of federalism is now being revived in the constitutional arrangements of several African countries. A number of them jumped on the bandwagon of federalism in the early 1990s because it came to be seen as a means to facilitate development, to counter the concentration of power in a single governmental actor and to manage communal tensions. An important part of the move towards federalism is the establishment of courts that are empowered to umpire intergovernmental disputes. This edited volume brings together contributions that first discuss questions of design by focusing, in particular, on the organisation of the judiciary and the appointment of judges in African federal systems. They then examine whether courts have had a rather centralizing or decentralizing impact on the operation of African federal systems"--